2016
DOI: 10.18569/tempus.v10i1.1860
|View full text |Cite
|
Sign up to set email alerts
|

Mediação: um meio de desjudicializar a saúde

Abstract: RESUMO: O artigo analisa o direito à saúde como direito fundamental inserto na Constituição do país e ainda não executado plenamente pelo Estado. Discute como as demandas tem superlotado os Tribunais de Justiça, provocando os gestores públicos governamentais, no âmbito do Sistema Único de Saúde, em busca de respostas as demandas sentidas pelos indivíduos, famílias e comunidades no tocante ao acesso as ações e serviços de saúde, ou seja, discorre sobre o que o cidadão de forma individual ou coletiva busca atrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…9 By providing the exercise of citizenship associated with the practice of the sanitary mediation, alternative dispute resolution method in the health sector adopted in the municipal secretaries, possibly, there will be a considerable reduction of disputes and judicial demands. 13,14 Of the universe of the judges interviewed, 20 (59%) responded that the judicialization is due to the management inefficiency and claimed that the demands that reach the judiciary could be resolved by the Executive Power, which, in turn, neglect the citizen attention, even the one already provided by means of the Public Policies. The management failures Another reason for the judicialization, according to the managers, are the prescribers, which, when coming from the SUS network, do not observe what already exists standardized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 By providing the exercise of citizenship associated with the practice of the sanitary mediation, alternative dispute resolution method in the health sector adopted in the municipal secretaries, possibly, there will be a considerable reduction of disputes and judicial demands. 13,14 Of the universe of the judges interviewed, 20 (59%) responded that the judicialization is due to the management inefficiency and claimed that the demands that reach the judiciary could be resolved by the Executive Power, which, in turn, neglect the citizen attention, even the one already provided by means of the Public Policies. The management failures Another reason for the judicialization, according to the managers, are the prescribers, which, when coming from the SUS network, do not observe what already exists standardized.…”
Section: Discussionmentioning
confidence: 99%
“…19 Even by realizing, the budget planning to implement the public health policy this can be impaired by legal decisions that can ensure the right of one, obliging the management to stop improving such questions in the basic attention programs. 13,17,20 Among the managers, 24 (20%) see the judicialization as a risk for the SUS conceptions, since the principle of equality is not observed, the waves regulatory mechanism is amended, making planning impossible, leaving without control the budget and financial forecasting, as shown in the speech of Manager 4: "The deviation from a financial flow that could help thousands of people, prevention projects support is intended to comply with legal measures. In addition to interfering in the public management planning, the legal decisions impact on guarantee of the right to health of the collectivity.…”
Section: Mediation and Judicialization Of Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Oliveira et al, studies on health judicialization have increased every year, demonstrating the importance of topic 3 , which is also supported by the study by Araújo et al 4 . The main issue in this area has been the access to medicines -Oliveira et al 5 , for example, concluded that 60% of the publications analyzed dealt with the topic.…”
mentioning
confidence: 99%